PEREMPUAN MEMINANG LAKI-LAKI MENURUT HADIS - Robiah Awaliyah; Wahyudin Darmalaksana (UIN Sunan Gunung Djati Bandung, 2020)
This study aims to discuss the diversity of Muslim understanding in addressing the hadith about the engagement of women against men in the modern era. This research is a qualitative type which applies a literature study to interpret matan (hadith text) using the method of syarah approach. The results and discussion of this study include the engagement (khitbah) in Islam, the views of ulama on the syarah hadith, and an analysis of the diversity of Muslim understanding from a cultural perspective. This study concludes that the diversity of Muslim understanding in addressing the hadith about the engagement of women to men can be overcome through the completion of Islamic law, but this is even more flexible approached with a cultural perspective. This study recommends that further research be undertaken on the hadith on the engagement of women against men through field studies with an ethnographic analysis approach.